THE INFLUENCE OF ISLAMIC TEACHINGS ON THE POLITICAL ATTITUDES AND GOVERNANCE PRACTICES OF MUSLIMS IN MACEDONIA: A SOCIOLOGICAL PERSPECTIVE (Religious dialogue and cooperation, 2025)
This research investigates the influence of Islamic teachings on the political attitudesand governance-related practices of Muslims in North Macedonia. Focusing on the intersection ofreligion and politics, the study examines how Islamic principles shape perspectives on democracy,participation in elections, voting behavior, and engagement in political life. Using survey data collectedfrom Muslim communities, the research explores the extent to which religious beliefs informdecisions to participate in or abstain from political processes, as well as perceptions of governancewithin the framework of Islamic values. By narrowing its focus to the sociological institution ofpolitics and governance, this study provides valuable insights into the role of religion in shapingpolitical behavior and attitudes in a diverse and multi-religious society.
Keywords: Islamic teachings; politics; governance; political participation; religion and politics